The need for autonomous vocabulary learners in the Malaysian ESL classroom - Naginder Kaur (Penerbit UKM, 2013)
One of the many predicaments faced by language learners at all levels is lack of lexical competence, resulting in lagging proficiency levels and inability to relate to the four language skills. There are many factors which explain this state, one of which is the learner variable. The learner is deemed to be of utmost importance because it is ultimately the learner who has to learn for himself and by himself. In view of this, fostering learner autonomy is becoming one of the most important goals in language teaching as the ultimate goal of education is to produce lifelong learners who are able to learn autonomously. This paper proposes that in the Malaysian context, as is elsewhere, it is imperative that we train our learners to become autonomous in realising the National Education Philosophy which espouses lifelong learning. By learning vocabulary autonomously, several benefits are derived, namely, learners can improve both receptive and productive language skills, consequently see improvement in language proficiency. Good language proficiency also ensures the ability to respond appropriately to the pervading era of knowledge economy and globalisation, which will in turn, enable Malaysian learners to be assured of employability. Hence, the initial seed of autonomous learning of vocabulary must be planted by the learner to ensure a fruitful harvest at all stages of learning and post-learning.